Livelihoods, poverty, and food insecurity in Myanmar: Household survey evidence from May 2021 - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Six rounds of the Rural-Urban Food Security Survey (RUFSS) conducted in 2020 demonstrated the impacts of the COVID-19 crisis on poverty and food insecurity among approximately 2,000 households with pregnant women or young children in urban Yangon and the rural Dry Zone. In this Research Note, we present results from a follow-up round conducted in May 2021.